2022
DOI: 10.2196/38608
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cognitive Behavioral Therapy for Insomnia to Improve Sleep Outcomes in Individuals With a Concussion: Protocol for a Delayed Randomized Controlled Trial

Abstract: Background Sleep disturbances post concussion have been associated with more frequent and severe concussion symptoms and may contribute to poorer recovery. Cognitive behavioral therapy for insomnia (CBT-I) is an effective treatment for insomnia; however, it remains unclear if this treatment method is effective in improving sleep outcomes and reducing concomitant postconcussion symptoms. Objective The hypotheses for this study are that (1) CBT-I will imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Detailed methods, which are described below, for this study can be found in Ludwig et al 16 This study was approved by the Institutional Review Board at the University of Kansas Medical Center. Prior to study procedures, individuals completed an informed consent process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed methods, which are described below, for this study can be found in Ludwig et al 16 This study was approved by the Institutional Review Board at the University of Kansas Medical Center. Prior to study procedures, individuals completed an informed consent process.…”
Section: Methodsmentioning
confidence: 99%
“…Study flow. From Ludwig et al16 Originally published in JMIR Research Protocols (https://www.researchprotocols.org), September 23, 2022. Published (and can be reproduced) under the terms of Creative Commons Attribution 4.0 license (or 2.0 prior to mid-May 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation